A dendeicultura em Igarapé-Açu/Pará: um olhar sobre as relações de trabalho que tipificam o trabalhador rural na Agroindustrial Palmasa - CARDOSO, Marlon Kauã Silva (Universidade Federal do Pará, 2025)
The objective of this research was to analyze the work relationships that characterize rural workers in the palm oil agroindustry in Igarapé-Açu, notably analyzing Agroindustrial Palmasa. The palm oil agroindustry, at a macropolitical level, was territorialized in the northeast of Pará through state developmental actions in civil-military governments in the 1960s, planned by the Superintendence for Economic Valorization of the Amazon (SPVEA) and the Superintendency for the Development of the Amazon (SUDAM), and, it has a new impulse with the neo-developmentalism of the 2000s, associated with sustainable development, through the National Biodiesel Production Program (PNPB) and the Sustainable Palm Oil Program (PSOP). These led to integration projects, to obtain the Social Fuel Seal (SCS), between palm oil producers and family farmers in municipalities in the northeast of Pará. Through qualitative methodology, combining interview, bibliographic and quantitative data, we verified that the most recent public policies did not cover the economic activities of Agroindustrial Palmasa, in Igarapé-Açu. In the region, contracts predominate, but only for purchase and sale, an associative relationship, between medium/large rural palm oil producers and the company itself. In this way, direct relations between classes gravitate between medium/large farmers and farm workers responsible for working on the farms.